Screening, Expression and Analysis of Enzymatic Properties of a Cold-active Lipase-producing Strain - Linlin XU; Huiqian LIU; Mengyao ZHANG; Huijing ZHANG; Jiaxing LI; Chenchen QI; Chengtao WANG (Shipin gongye ke-ji, 2024)
High-yield strains of cold-active lipase are screened to provide production information for the industrial development of lipase. A cold-active lipase-producing strain was isolated from Xing'an larch forest soil in Mohe County using the Rhodamine B plate method. Its morphological, physiological, and biochemical characteristics were identified, and combined with the 16S rDNA gene sequence, the strain was determined to be Bacillus thuringiensis. The lipase gene Lip240 was cloned using the Bacillus thuringiensis genome as a template, and heterologous expression and enzymatic properties of Lip240 were analyzed. The results showed that the recombination lipase Lip240 had an optimal reaction temperature of 30 ℃, and could maintain more than 60% activity when treated at 4~30 ℃ for 6 hours, thus a cold-active lipase. Besides, its optimal pH was 8.0. Additionally, Ca2+, Mn2+, Fe2+, Fe3+, and Cr3+ had a certain enhancing effect on the activity of Lip240. Notably, Lip240 had a good organic solvent tolerance, while SDS could significantly (P<0.05) inhibit its activity. Lip240 exhibited good substrate specificity towards medium and short-chain substrates. The conclusions of this study would provide a theoretical basis for the development and utilization of microbial resources and the industrial application of cold-active lipase.